Evolution of geodynamic processes in Neoarchean Kadiri greenstone belt, eastern Dharwar Craton, India: Implications on the migrating arc magmatism. (May 2020) - Manikyamba, C.; Pahari, Arijit; Dhanakumar Singh, Th.; Chatterjee, Adrija; Ganguly, Sohini
Graphical abstract: Highlights: Geochemical imprints of subduction-zone volcanism in the lithounits of Kadiri Greenstone belt. Nb-enriched basaltic andesites, Mg-andesites represent the progressive stage of subduction. Arc migration towards the continent and became active continental margin. Abstract: Dharwar Craton of southern peninsular India is one of the significant Archean cratons in the world with well developed greenstone belt sequences representing plume-arc accretionary tectonics. The eastern Dharwar Craton (EDC) is endowed with excellent gold mineralization which is being mined and the greenstone belt lithounits among which majority of them represent the convergent margin processes. The Neoarchean Kadiri greenstone belt of EDC consists of an array of mafic, intermediate and felsic volcanic rocks among which the mafic rocks exhibit a wide range of silica (49.74–65.19 wt.%), high LILE, HFSE including the Nb contents (7−15 ppm) that are classified as Nb-enriched basaltic andesites (NEBA). Moderate composition of SiO2 (57−63 wt.%) along with higher MgO (3.96–7.58 wt.%), Cr (44−890 ppm) and Ni (22−491 ppm) contents distinguish some of the intermediate rocks as Mg-andesites. The petrographic characteristics along with higher silica (63−75 wt.%), Na2 O (2.21–4.01 wt.%) and low K2 O (0.7–3.35) classify the associated felsic volcanic rocks as sodic adakites. Abundance of K-feldspar phenocrysts and higher K2 O content (1.19–7.0 wt.%) in some adakites identify them as potassic adakites. The geochemical characteristics of the calc-alkaline andesite-dacite-rhyolites (ADR) reflect on typical island arc environment involving the processes of fractional crystallization and crustal contamination in an active continental margin environment. The NEBA and Mg-andesites are the products of hybridized mantle wedge under the influence of slab fluids/melts whereas the Na-adakites are the slab melts erupted within the oceanic domain and the K-adakites were emplaced under the influence of continental crust during the migration of the island arc towards the continental margin. Beside the generation of various types of volcanic rocks, these convergent margin processes have played a significant role in the generation and mobilization of gold mineralized fluids, which are being mined from some greenstone belts of EDC.